Evaluation of the effectiveness of clinical and radiographic analysis for the diagnosis of proximal caries for different clinical experience levels: comparing lesion depth through histological analysis - Leila Abou Hala; José Benedicto Mello; Pedro Luiz Carvalho (Universidade Estadual de Campinas, 2015)
Proximal cavity lesions are difficult to diagnose and are also hard to examine due to their location. Radiographic examination and teeth separation are resources used to help in caries diagnosis. The aim of this study was to evaluate, in different professional experience levels, the effectiveness of clinical and radiographic examinations in diagnosing proximal cavities, comparing lesion depth considered in these examinations to histological examinations. Thirty nine human teeth were used, 20 premolars and 19 molars, with clinical alterations on one proximal surface, such as lesions with either white or brownish stains and small cavitations which showed no clinical signs on the occlusal face, causing the professional insecurity in performing an accurate diagnosis as well as appropriate treatment. Samples were made using x-ray interproximal technique. Forty professionals of different experience levels performed clinical and radiographic examinations of the samples by filling out a form after classifying lesions depth. The samples were later sectioned for a histological analysis. Results showed that there was great variability on answers to examinations, with a low agreement percentage among examiners. After concluding all evaluated examinations, the examiners were not able to come up with an accurate diagnosis of lesions conditions on proximal cavities. The rate of cavitation was greater in lesions found on the external half of dentine, surpassing the amelodentinal limit, and an agreement percentage to conventional and digital x- ray examinations were equivalent.